2011
DOI: 10.1007/978-3-642-23508-5_218
|View full text |Cite
|
Sign up to set email alerts
|

2D-Tasks for Cognitive Rehabilitation

Abstract: Abstract-Neuropsychological Rehabilitation is a complex clinic process which tries to restore or compensate cognitive and behavioral disorders in people suffering from a central nervous system injury. Information and Communication Technologies (ICTs) in Biomedical Engineering play an essential role in this field, allowing improvement and expansion of present rehabilitation programs. This paper presents a set of cognitive rehabilitation 2D-Tasks for patients with Acquired Brain Injury (ABI). These tasks allow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, one research paper indicated the successful transfer of skills following the completion of a 20-session problem-solving program on an interactive rehabilitation platform called PREVIRNEC remotely monitored by therapists (Soong & Man, 2006). The initial findings indicated that 90.24% of participants with TBI reported some degree of cognitive improvement in a clinical trial of the cognitive tasks on the PREVIRNEC platform (Hernández et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one research paper indicated the successful transfer of skills following the completion of a 20-session problem-solving program on an interactive rehabilitation platform called PREVIRNEC remotely monitored by therapists (Soong & Man, 2006). The initial findings indicated that 90.24% of participants with TBI reported some degree of cognitive improvement in a clinical trial of the cognitive tasks on the PREVIRNEC platform (Hernández et al, 2012).…”
Section: Introductionmentioning
confidence: 99%